Synthesis of MOF-199 and application to CO2 adsorption - Nguyen Thi, Thuy Van; Luu, Cam Loc; Hoang, Tien Cuong; Nguyen, Tri; Bui, Thanh Huong; Duy Nguyen, Phuc Hoang; Pham Thi, Thuy Phuong (Advances in natural sciences. Nanoscience and nanotechnology, 2013)
In this study a metal-organic framework (MOF-199) has been synthesized by solvent-thermal method. The conditions of preparation and activation processes have been investigated. The obtained material was characterized by methods of x-ray diffraction (XRD), infrared (IR) spectroscopy, thermogravimatric analysis (TGA) and scanning electron microscopy (SEM). The CO2 adsorption measurements were carried out on a high pressure volumetric analyzer (Micromeritics HPVA − 100). According to experimental results, Cu(NO3)2·3H2O has been shown to be the best copper(II) precursor for the synthesis of MOF-199 and N,N-dimethylformamide (DMF):C2H5OH:H2O with the ratio of 1:1:1 has been chosen as the most suitable solvent. The appropriate activation condition has been determined as follows: activate at 200 °C for 5 h and use CH3OH as the solvent to remove DMF. At the optimal conditions, an octahedral shape and three-dimensional (3D) structure of crystallite of MOF-199 was obtained. The synthesized MOF-199 expressed a high value of specific surface area (1448 m2 g−1 by Brunauer-Emmet-Teller (BET) method and 2028 m2 g−1 by Langmuir method) with Ta porous size of crystal of 11.8 Å and specific volume of 0.693 cm3 g−1; it was still stable up to 332 °C and its CO2 storage capacity reached to 206.59 cm3 (STP) g−1 at 25.76 bar.